Cancer Supportive and Survivorship Care in Singapore: Current Challenges and Future Outlook - Kiley Wei-Jen Loh; Terence Ng; Su Pin Choo; Hay Mar Saw; Rathi Mahendran; Celia Tan; Gail Chia Yang Chang; Yew Jin Ong; Alethea Chung Pheng Yee; Alexandre Chan; Khee Chee Soo (Journal of Global Oncology, 2018)
Despite being a relatively young nation, Singapore has established itself as a leading multifaceted medical hub, both regionally and globally. Although Singapore continues to pursue excellence in oncology care, cancer supportive care and survivorship care remain in the infancy stage. In an effort to advance this important aspect of oncology care in Singapore, the first cancer supportive and survivorship care forum was held in December 2016, involving 74 oncology practitioners. The primary goals of this forum were to raise awareness of the importance of cancer supportive and survivorship care and to provide a platform for oncology practitioners of diverse backgrounds to converge and address the challenges associated with the delivery of cancer supportive and survivorship care in Singapore. Key challenges identified during this forum included, but were not limited to, care fragmentation in an oncologist-centric model of care, poor integration of allied health and rehabilitation services, passive engagement of community partners, lack of specialized skill sets and knowledge in supportive and survivorship care, and patient-related barriers such as poor health literacy. The survivorship care model commonly used in Singapore places an imbalanced emphasis on surveillance for cancer recurrence and second primary cancers, with little attention given to the supportive and survivorship needs of the survivors. In summary, these challenges set the stage for the development and use of a more survivor-centric model, one that focuses not only on cancer surveillance, but also on the broad and unique physical and psychosocial needs of survivors of cancer in Singapore.